Abstracts from JADPRO Live 2018 (J Adv Pract Oncol, 2018)
Abstracts from JADPRO Live 2018 THE DIPLOMAT HOTEL, HOLLYWOOD, FLORIDA • NOVEMBER 1–4, 2018 The posters for the abstracts below can be found at eventscribe.com/2018/posters/JADPROLIVE/home.asp.